2014
DOI: 10.1002/2014gc005560
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and eruptive activity along the East Pacific Rise at 16°N, in relation with the nearby Mathematician hotspot

Abstract: The 16 N segment of the East Pacific Rise is the most overinflated and shallowest of this fastspreading ridge, in relation with an important magma flux due to the proximity of the Mathematician hotspot. Here, we analyze the detailed morphology of the axial dome and of the Axial Summit Trough (AST), the lava morphology, and the geometry of fissures and faults, in regard to the attributes of the magma chamber beneath and of the nearby hotspot. The data used are 1 m resolution bathymetry combined with seafloor ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 60 publications
6
31
0
Order By: Relevance
“…We present a detailed tectonic analysis of the 16°N segment of the EPR using near‐bottom microbathymetry, photographs, videos, and direct visual observations made from a submersible. These detailed analyses extend the morphological descriptions presented by Le Saout et al (). These new data allow us to evaluate the small‐scale interactions between volcanic and tectonic processes near ASTs, the nucleation and evolution of faulting patterns, and the distribution of tectonic strain in the context of an unusual spreading segment influenced by a hot spot.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…We present a detailed tectonic analysis of the 16°N segment of the EPR using near‐bottom microbathymetry, photographs, videos, and direct visual observations made from a submersible. These detailed analyses extend the morphological descriptions presented by Le Saout et al (). These new data allow us to evaluate the small‐scale interactions between volcanic and tectonic processes near ASTs, the nucleation and evolution of faulting patterns, and the distribution of tectonic strain in the context of an unusual spreading segment influenced by a hot spot.…”
Section: Introductionsupporting
confidence: 83%
“…Between 15°36′N and 15°53′N, based on data from Macdonald et al () and Carbotte et al (), and on high‐resolution bathymetry and videos (the same used in our present study), Le Saout et al () identified six 4–9.5 km long third‐order spreading segments referred as subsegments (Figure ). These subsegments are characterized by 10 distinct well‐defined ASTs of variable depth (1 to 40 m) and width (10 to 1,000 m).…”
Section: Geological Contextsupporting
confidence: 50%
See 2 more Smart Citations
“…It still falls far short of the estimated 11 km off axis advance of the 220 km 2 flow at 8°S (Macdonald et al, ). As Escartin et al () and Le Saout et al () note, the advance of off‐axis flows is stopped when they reach a fault too tall to overtop. The flows mapped on AR3 extend 3.5 km to the scarp at the base of the next older abyssal hill to the west, where the crustal age is inferred to be about 190 ka.…”
Section: Discussionmentioning
confidence: 99%